PENGARUH PENYULUHAN TERHADAP PENINGKATKAN PEMAHAMAN KELOMPOK TANI DAN KADER TUBERCULOSIS TERHADAP PENYAKIT TUBERCULOSIS, PENGOBATAN DAN PENCEGAHANNYA - Abdul Rahem; Wahyu Utami; Liza Pristianty; Andi Hermansyah; Anila Impian Sukorini; Titik Puji Rahayu; Ana Yuda; Arie Sulistyarini; I Nyoman Wijaya; Gusti Noorrizka V; Yuni Priyandani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Tuberculosis is an infectious disease which ranks second as the cause of death in the infectious disease class after infection of Human Immunodeficiency Virus. Countries contributing to the largest cases of tuberculosis starting from the highest order are India, Indonesia, China, the Philippines and Pakistan. East Java is in second place after West Java Province. Sumenep Regency, ranks first in East Java Province in 2019. Sumenep Regency, has 126 islands, of which 48 islands are inhabited by the community. In mainland Sumenep, the most cases of pulmonary tuberculosis are located in Bluto District, one of the endemic areas. Therefore, community service by a team of lecturers from the Faculty of Pharmacy, Airlangga University, Surabaya was carried out in Bluto District, Sumenep Regency. This targets four categories of Sustainable Development Goals, namely Good health and well-being; Quality education; Peace, justice and strong institutions; and Partnership for the goals. Besides that, this community service targets achievement on Key Performance Indicators 2, 3, 5 and 7. The four KPIs characterize off-campus activities and involvement with the community. Therefore, this community service formulates a comprehensive and systematic approach in responding to problems related to the TB infectious disease. The community service was carried out for two days, namely on Saturday and Sunday, September 10-11 2022 at Kampung Negara, Bungbungan Village, Bluto District, Sumenep Regency. The participants in this first year were farmer groups and health center staff, as well as pharmacists who practice in various health facilities serving TB patients. From the results of the evaluation through a questionnaire with statistical analysis, and the results of the discussion it can be concluded that this counseling is very useful for participants according to their confession and can increase participants' understanding of TB disease, its treatment and prevention.